The Perspectives Associated With the Computer-Based Diagnostic Method of Depressive Disorder - Bartkiene, Elena; Steibliene, Vesta; Adomaitiene, Virginija; Lele, Vita; Cernauskas, Darius; Zadeike, Daiva; Klupsaite, Dovile; Juodeikiene, Grazina (Frontiers in Psychiatry, 2018)
Depressive disorder (DD) shortens a healthy and productive human life and leads to significant public health costs and high suicide rates. In a depressed person, a lack of emotions is visible in expression and behavior, with low energy, high tension, weakened sense perception, and loss of food taste. We hypothesize that the measure of a patient’s facial expressions and emotional response to different tastes of food can be used as a diagnostic moderator for the development of a new contactless, computer-based diagnostic method for DD. The confirmation of a diagnostic hypothesis of DD using facial and emotional expressions as responses to different tastes of food can shed new perspectives on early contactless, computer-based psychiatric diagnostic strategies and early identification of suicidal tendencies, which is an important issue in public mental health.